(2-12/x+3):x²-6x+9/x²-9
Renata ajutooorrrrr
Anexe:
mihaelaivan07112003:
renate ajutor
Răspunsuri la întrebare
Răspuns de
1
amplificãm pe 2 cu x^2-9 si pe 12/(x+3) cu x-3
E(x)=[(2x^2-18-12x+36)/(x^2-9)]:(x^2-6x+9)/(x^2-9)
E(x)=(2x^2-12x+18)/(x^2-9)×(x^2-9)/(x^2-6x+9)
E(x)=(2x^2-12x+18)/(x^2-6x+9)
E(x)=2(x^2-6x+9)/(x^2-6x+9)
E(x)=2 € N
E(x)=[(2x^2-18-12x+36)/(x^2-9)]:(x^2-6x+9)/(x^2-9)
E(x)=(2x^2-12x+18)/(x^2-9)×(x^2-9)/(x^2-6x+9)
E(x)=(2x^2-12x+18)/(x^2-6x+9)
E(x)=2(x^2-6x+9)/(x^2-6x+9)
E(x)=2 € N
Alte întrebări interesante
Matematică,
8 ani în urmă
Biologie,
8 ani în urmă
Franceza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă